The state of Language Testing in Italy and New Perspectives in Latin America - Machetti, Sabrina (2025)
Language Testing is a rather new field in the Italian context. The reasons are varied and range from cultural to linguistic ones. Interest in the field sparked in the 90s when institutions began to provide an official answer to the needs of learners who were not approaching the Italian language only for cultural or personal reasons, but for specific needs of various kinds. The official L2 Italian qualifications are now 4 (CILS, CELI, CERT.IT, PLIDA) and show different trends in different areas of the world. This diversification is mainly linked to individual agreements and individual projects. The presence of many Italian emigrant descendants confirms Latin America as one of the geographic areas where strong personal motivation in the study of the Italian language persists. In Language Testing and Assessment, there is a potentially growing catchment area based on the need to create agreements at the local level. This study aims to report on the state of the art of Language Testing and Assessment in Italy and the diffusion of Italian language certifications in Latin America administering CILS exams from 1993 to date to reflect on the profile of the target audiences.